1996
DOI: 10.1161/01.cir.94.11.2837
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Oxidation Enzyme Gene Expression Is Downregulated in the Failing Heart

Abstract: These findings identify a gene regulatory pathway involved in the control of cardiac energy production during the development of HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
430
3
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 617 publications
(470 citation statements)
references
References 34 publications
36
430
3
1
Order By: Relevance
“…Reports of patients and animal models with heart failure have consistently shown that the myocardium switches to increased dependency on glucose as the substrate during cardiac hypertrophy and failure (29). This metabolic shift coincides with a down-regulation of expression of fatty acid oxidation enzymes and has been interpreted as a reactivation of the fetal gene expression program (31). The knockout mice of this study display an early onset of reduced expression of PPAR␣ transcripts, encoding the major regulator of the fatty acid oxidation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of patients and animal models with heart failure have consistently shown that the myocardium switches to increased dependency on glucose as the substrate during cardiac hypertrophy and failure (29). This metabolic shift coincides with a down-regulation of expression of fatty acid oxidation enzymes and has been interpreted as a reactivation of the fetal gene expression program (31). The knockout mice of this study display an early onset of reduced expression of PPAR␣ transcripts, encoding the major regulator of the fatty acid oxidation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…After birth, the capacity for PPAR-␣-dependent FAO increases markedly. This results in the heart using FAO as the preferred substrate for ATP production while retaining the ability to switch to glucose and lactate utilization to meet its energy demands with varying dietary and physiological conditions (74,94). Studies using cultured neonatal cardiomyocytes have demonstrated the direct effects of fatty acids and PPAR-␣ agonists in activating PPAR-␣-dependent enzymes of fatty acid uptake and FAO in the heart (10,91,92).…”
Section: Ppar-␣ and The Heartmentioning
confidence: 99%
“…In conditions of pressure-induced cardiac hypertrophy, PPAR-␣ is downregulated, resulting in reversion of the heart to the fetal pattern of glucose and lactate substrate utilization (4,74). Diminished cardiac FAO and increased utilization of glucose has been found in studies of both murine (73) and human (19) cardiac hypertrophy.…”
Section: Ppar-␣ and The Heartmentioning
confidence: 99%
“…Isolated mitochondria from Cn*-expressing hearts demonstrated impaired oxidative function (16). These latter observations are inconsistent with the known metabolic responses in skeletal muscle given that, during pathological hypertrophic growth, the heart undergoes a reversion to a fetal energy metabolic program characterized by reduction of mitochondrial oxidative capacity and fatty acid utilization (17)(18)(19). In contrast, with physiological forms of hypertrophy such as following exercise training, Cn and CaMK are activated yet both contractile and metabolic function is preserved (20).…”
mentioning
confidence: 96%